Pengaruh Kualitas Layanan Terhadap Kepuasan Pelanggan Serta Dampaknya Pada Loyalitas Pelanggan E -Commerce Shopee - Sikki, Nurhaeni; Ernawati, Ernawati; Kartina, Hana Betel; Jacob, Lodia Antonia; Nasution, Caesar Rayhand Arrafif; Suriansyah, Suriansyah; Lusito, Tri Astrit; Prasetyo, Tri Wahyu (Jurnal Nasional Manajemen Pemasaran dan SDM, 2024)
This study investigates the impact of service quality on customer satisfaction and its subsequent effect on Shopee e-commerce customer loyalty. Primary data were collected through questionnaires distributed to respondents and analyzed using path analysis with the SmartPLS 3.0 application. The findings indicate that service quality plays a significant role in influencing customer satisfaction, highlighting its importance as a key determinant in the e-commerce service landscape. However, the research also reveals that service quality does not directly affect customer loyalty. Instead, customer satisfaction acts as a critical mediator that significantly influences customer loyalty. These insights suggest that while improving service quality is essential, fostering customer satisfaction is even more pivotal for retaining loyal customers in the competitive e-commerce market. By focusing on enhancing the overall satisfaction of its users, Shopee can strengthen customer loyalty and maintain its competitive edge. The study underscores the interconnectedness of these factors and provides valuable recommendations for businesses aiming to improve customer experiences and sustain long-term growth in the digital marketplace.